Increased Neutrophil Respiratory Burst Predicts the Risk of Coronary Artery Lesion in Kawasaki Disease - Hu, Jing; Qian, Wei; Yu, Zhiwei; Xu, Tao; Ju, Liang; Hua, Qi; Wang, Yan; Ling, Jing Jing; Lv, Haitao (Frontiers in Pediatrics, 2020)
Background: Kawasaki diseases (KD) is a febrile systemic vasculitis in infants associated with coronary aneurysm. The etiology of KD remains unclear. Human neutrophils have great capacity to cause tissue damage in inflammatory diseases via their inappropriate activation to release reactive oxygen species (ROS). Brain natriuretic peptide (BNP) is a substantial modulator of neutrophil activation to regulate ROS production. It is increasingly released from the myocardium in heart failure and myocardial inflammatory states. Objective: The purpose of this study was to explore the potential role of neutrophil in the pathogenesis of coronary artery lesions (CAL) in KD. Materials and methods: A total of 78 children were enrolled. Of all the cases, 20 cases are healthy control (HC), 20 are with coronary artery lesion (CAL), 38 are with non-coronary artery lesion (NCAL). The activation ratio of neutrophils was evaluated by flow cytometry. In addition, plasma levels of BNP were detected. Results: Our results showed that the activation ratio of neutrophils in KD with CAL is significantly higher than other two groups (HC and NCAL). Besides, the plasma levels of BNP in KD (with or without CAL) were higher than that in HC. Conclusions: These findings suggested that neutrophil respiratory burst may play a significant role in the pathogenesis of CAL, and predicts the risk of CAL in Kawasaki disease.